Immune landscape and TAM density in endometrial cancer: implications for immune checkpoint inhibitors efficacy - Olivia Le Saux; Renaud Sabatier; Isabelle Treilleux; Léa-Isabelle Renaud; Pierre-Emmanuel Brachet; Alejandra Martinez; Jean-Sébastien Frenel; Cyril Abdeddaim; Justine Berthet; Sarah Barrin; Amélie Colombe-Vermorel; Laetitia Odeyer; et al. (Therapeutic Advances in Medical Oncology)
Background: Immune checkpoint inhibitors (ICIs) have shown efficacy in endometrial cancer (EC); however, their efficacy varies according to mismatch repair (MMR) status. Notably, even among patients with MMR-deficient (MMRd) or microsatellite instability-high (MSI-H) tumors, approximately one-third exhibit primary resistance to ICI monotherapy. Objectives: We aimed to characterize dissimilarities in the tumor immune microenvironment of ICI-treated MMRd/MSI-H versus MMR-proficient (MMRp)/microsatellite stable (MSS) EC, and to identify mechanisms of resistance. Design: Adults with histologically confirmed advanced or recurrent EC treated with ICIs in 6 French comprehensive cancer centers were included. Patients without available archival formalin-fixed paraffin-embedded primary tumor samples were excluded. Clinical data were collected retrospectively. Methods: Patients were classified as ICI-Responders or Non-Responders based on best objective response. A seven-color multi-immunofluorescence staining (CD20, CD4, CD8, FoxP3, CD68, CK, and DAPI) was performed on sections from archival formalin-fixed paraffin-embedded primary tumors. Cell densities and spatial proximity were analyzed using inForm software. T/B lymphoid aggregates (LA) and tertiary lymphoid structures (TLS) were separately quantified. Microsatellite status, presence of LA/TLS, and immune cell densities were correlated to response to treatment. Results: Twenty-one MMRd/MSI-H and 12 MMRp/MSS tumors were analyzed. We observed more MMRd/MSI-H tumors with LA/TLS compared to MMRp/MSS cases: 81% versus 17%, p  ⩽ 0.001. There were more CD8 + T effector cells in the vicinity of B cells in MMRd/MSI-H tumors compared to MMRp/MSS tumors (1.26 (0–3.40) vs 0.49 (0–1.86), p  = 0.017), suggesting cooperation between CD8 + T cells and B cells in MMRd/MSI-H tumors. No differences were shown in terms of the presence of LA/TLS and the subsequent response to ICI in EC ( p  = 0.400). Using a multivariate logistic regression model, we found that a low density of CD68 + tumor-associated macrophages (TAMs) in the stroma, was associated with response to ICI in EC (odds ratio = 11.67, 95% CI (1.69–237.45), p  = 0.033) and showed good accuracy in predicting response to ICI in the whole cohort (AUC = 0.75, 95% CI (0.59–0.91)). Conclusion: We characterize the immune landscape in EC patients treated with ICIs. Distinct immune infiltrate patterns were observed in MMRd/MSI-H and MMRp/MSS tumors. A significant negative association between TAM density and ICI response was shown.